Why don't worms have legs? - Vaughan, Jenny (Milwaukee, Wis. : G. Stevens, 2004)
Explains, in simple text and illustrations, the behavior and characteristics of animals that live in gardens, such as how spiders make webs, why gardeners like ladybugs, and what ants do all day.
First published in Great Britain in 2003 by ticktock Media, Tunbridge Wells, Kent, England.
Includes index.
4.0
K-3
Keywords: Garden animals -- Juvenile literature; Animals; Arthropods; Garden animals; Insects; Animals; Arthropods; Garden animals; Insects